2021
DOI: 10.1016/j.jaad.2021.03.050
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2a randomized, placebo-controlled study to evaluate the efficacy and safety of the oral Janus kinase inhibitors ritlecitinib and brepocitinib in alopecia areata: 24-week results

Abstract: Background: Alopecia areata (AA) is an autoimmune form of hair loss with limited treatments.Objective: To evaluate the efficacy and safety of the Janus kinase inhibitors ritlecitinib and brepocitinib in patients who have AA with $ 50% scalp hair loss.Methods: Patients were randomized to once-daily ritlecitinib, brepocitinib, or placebo. The primary efficacy endpoint was a 24-week change from baseline in the Severity of Alopecia Tool (SALT) score. The key secondary efficacy endpoint was the proportion of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
181
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(220 citation statements)
references
References 24 publications
7
181
0
6
Order By: Relevance
“…Evidence for therapeutic efficacy of JAK inhibitors has also been demonstrated in conditions such as alopecia areata, vitiligo and palmoplantar pustulosis 85 , 86 . In a phase II trial for treatment of alopecia areata, ritlecitinib (a JAK3 inhibitor) and brepocitinib showed marked efficacy and good tolerability after 24 weeks of treatment 87 .…”
Section: Jak Inhibition In Other Diseasesmentioning
confidence: 99%
“…Evidence for therapeutic efficacy of JAK inhibitors has also been demonstrated in conditions such as alopecia areata, vitiligo and palmoplantar pustulosis 85 , 86 . In a phase II trial for treatment of alopecia areata, ritlecitinib (a JAK3 inhibitor) and brepocitinib showed marked efficacy and good tolerability after 24 weeks of treatment 87 .…”
Section: Jak Inhibition In Other Diseasesmentioning
confidence: 99%
“…Recent work showed that the inflammation in LP is dominated by an IFN-γ and an IL-21 signature, along with an increased expression of phospho-STAT1 in the dermal infiltrate ( 200 ). In another T-cell mediated inflammatory skin disease, namely alopecia areata, the identification of an IFN gene signature in affected skin identified JAK inhibitors as potential new treatments for alopecia areata, which showed efficacy in phase 2 clinical trials ( 201 , 202 ). Based on these morphological observations and considerations, the authors concluded that use of JAK inhibitors may be beneficial in LP ( 200 ).…”
Section: Managementmentioning
confidence: 99%
“…To the Editor: Key findings from a 24-week, doubleblind period (DBP) of a phase 2a study (NCT02974868) indicated that the oral Janus kinase (JAK) inhibitors ritlecitinib (inhibits JAK3 and tyrosine kinase expressed in the hepatocellular carcinoma family) and brepocitinib (inhibits tyrosine kinase 2 and JAK1) were efficacious and well tolerated over 24 weeks in patients with alopecia areata and $50% scalp hair loss. 1 The effects of withdrawing a JAK inhibitor following the treatment of alopecia areata have not been evaluated in a placebo-controlled trial, but uncontrolled studies of the JAK inhibitors ruxolitinib and tofacitinib have reported hair loss 8 weeks after treatment cessation. [2][3][4][5] In this phase 2a study, following the DBP and a 4-week washout period, patients continued to be part of a single-blind extension involving the same dosing regimen as that in the DBP: 200 mg of ritlecitinib once daily ( for 4 weeks), followed by 50 mg once daily ( for…”
mentioning
confidence: 99%